Predicting Smoking Intentions Among Indonesian Youth Using Structural Equation Modeling and the Theory of Planned Behavior - Suwanda Priyadi; Audi Ahmad Rikardi; Bayu Suseno; Lusi Nuryanti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: In this study, we aimed to predict smoking intentions among Indonesian youth using the Theory of Planned Behavior (TPB) within the context of global tobacco use. Our objective was to examine how attitude toward smoking, subjective norms, and perceived behavioral control shape youth smoking intentions, addressing gaps in prior Indonesian studies by leveraging nationally representative data and enhanced analytical methods. Methods: This cross-sectional study involved a secondary data analysis of the 2019 Global Youth Tobacco Survey (GYTS) conducted across Indonesia. A total of 9,992 youth participants were enrolled, and data were collected through structured questionnaires. Results: The primary outcome of the study was cigarette smoking intention, and the structural equation modelling revealed a good model fit (SRMR = 0.018, RMSEA = 0.028, TLI = 0.986, and CFI = 0.994). All of the predictors were statistically significant in predicting youth smoking intentions. When compared to other TPB constructs, perceived behavioral control emerged as the strongest predictor (? = 0.223, p < .001), followed by attitude (? = –0.202, p < .001) and subjective norms (? = 0.091, p < .001). Past smoking behavior was also the strongest predictor (? = 0.241, p < .001). The model explained 29.7% of the variance in smoking intention. Individuals who had a positive attitude towards smoking, were exposed to smoking in both public and private spaces, and thought quitting was difficult were more likely to intend to smoke. Conclusion: In conclusion, our study contributes to the understanding of youth smoking behavior by applying the TPB in the Indonesian context. These findings highlight the importance of behaviorally informed tobacco control interventions that address young people's perceptions of control and attitudes towards smoking, as well as the value of school-based programs, media literacy campaigns, and peer education strategies tailored to Indonesian culture.